The energy balance of the asymmetric combined inductive-capacitive RF discharge at low pressure - Zykov, A.V.; Polozhiy, K.I.; Farenik, V.I. (Вопросы атомной науки и техники, 2003)
The combined inductive-capacitive RF discharge at low gas pressure is considered for a case of collisionless ion motion. The power distribution model in the combined RF discharge in case of two asymmetric RF electrodes is developed in term of a ratio of the electrode areas and in term of a magnitude of applied RF voltage. We believe that power distributes on three parts: ionization and acceleration of ions in two electrode-sheath transitions. Two types of design is considered: with one and two RF generators. The dependencies of the dissipated RF power parts are obtained in terms of external discharge parameters. It is revealed an existence of a power maximum on acceleration of ions at electrode, which has a lower area. Been accorded expression for dependence of optimum discharge parameters. At using the power distribution model results the system parameter correlation’s have been obtained for a maximum process effectiveness of physical sputtering for systems on the basis of combined inductive-capacitive discharge. У роботі розглядається комбінований індукційно-ємнісної ВЧ розряд в області низького тиску робочого газу, коли іони досягають стінок розрядної камери без зіткнень. Для випадку асиметричних ВЧ електродів побудована феноменологична модель балансу потужності, що підводиться до ВЧ розряду в залежності від відношення площ ВЧ електродів і амплітуди прикладеного ВЧ потенціалу. Розглянуті два типи систем: з одним і двома ВЧ генераторами. Отримана залежність складових потужності, що поглинається в розряді в залежності від зовнішніх параметрів розряду. Виявлено існування максимума потужності на прискорення іонів на електрод меншої площі. Знайдена залежність положення даного максимума від параметрів системи. Результати можуть бути використані як при конструюванні й оптимізації розпилювальних систем на базі комбінованого розряду, так і для подальшого розвитку модельних уявлень про фізику ВЧ розрядів. В работе рассматривается комбинированный индукционно-емкостной ВЧ разряд в области низкого давления рабочего газа, когда уход ионов из плазмы на стенки разрядной камеры происходит без столкновений. Для случая асимметричных ВЧ электродов построена феноменологическая модель баланса подводимой к разряду ВЧ мощности в зависимости от отношения площадей ВЧ электродов и амплитуды приложенного ВЧ потенциала. Рассмотрены два типа систем: с одним и двумя ВЧ генераторами. Получены зависимости составляющих поглощаемой в разряде мощности в зависимости от внешних параметров разряда. Обнаружено существование максимума мощности на ускорение ионов на электрод меньшей площади. Найдена зависимость положения данного максимума от параметров системы. Результаты могут быть использованы как при конструировании и оптимизации распылительных систем на базе комбинированного разряда, так и для дальнейшего развития модельных представлений о физике ВЧ разрядов.